Pneumoperitoneum Does Not Influence Spread of Local Anesthetics in Midaxillary Approach Transversus Abdominis Plane Block: A Descriptive Cadaver Study. Issue 4 (1st July 2015) - Desmet, Matthias; Helsloot, Dries; Vereecke, Evie; Missant, Carlo; van de Velde, Marc
Abstract : Background and Objectives: The transversus abdominis plane (TAP) block can be used as part of a multimodal analgesia protocol after abdominal surgery. This study investigated whether a pneumoperitoneum during abdominal surgery influences the spread of local anesthetics. Methods: Nine fresh frozen cadavers were used for the study. Using an ultrasound-guided midaxillary technique, a unilateral TAP block–like injection with 20 mL of methylene blue dye was performed. After the injection, a pneumoperitoneum was immediately installed for 1 hour. After desufflation, this ipsilateral side was dissected, and a TAP block–like injection was performed on the contralateral side. One hour after injection, the contralateral side was also dissected. The anatomical dissection was used to determine the extent of dye spread and the nerves stained by the dye. Results: In none of the specimens did the dye reach the posterior origin of the transverse abdominal muscle. There was no statistically significant difference in the number of stained nerves and spread of the dye in the insufflated side compared with the noninsufflated side. In 4 of 9 cadavers, we found a variant course of a nerve preventing staining of that nerve. Conclusions: The stretch of the abdominal wall caused by the insufflation of the abdomen does not influence the spread of dye in the abdominal wall. Because of the absence of posterior spread, regardless of the timing of a midaxillary ultrasound-guided approach, we believe that a posterior approach should be chosen if posterior spread is desired.